Aesthetic Procedures and Psychological Wellbeing in Saudi College Students: An In-Depth Exploration - Bin Rubaian NF; Elfaki AM; Almuhaidib SR; Aldulijan FA; Qasim RS; Nagshabandi KN; Al-Ojail HY; Alsubaie SS (Dove Medical Press, 2024)
Nouf F Bin Rubaian,1 Abdelaziz M Elfaki,2 Serene R Almuhaidib,3 Fajar A Aldulijan,4 Raghda S Qasim,3 Khalid Nabil Nagshabandi,5 Heba Yousef Al-Ojail,6 Shayma S Alsubaie7 1Department of Dermatology, King Fahad University Hospital, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2Healing Icon Center, Al Khobar, Saudi Arabia; 3Department of Dermatology, Dammam Medical Complex, Dammam, Saudi Arabia; 4Department of Family Medicine, Johns Hopkins Aramco Healthcare, Dhahran, Eastern Province, Saudi Arabia; 5Department of Dermatology, College of Medicine, King Saud University Medical City (KSUMC), Riyadh, Saudi Arabia; 6Department of Dermatology, King Faisal University, Al Ahsa, Saudi Arabia; 7King Fahad University of Petroleum and Mineral, Interdisciplinary Research Center for Finance and Digital Economy, Dhahran, Saudi ArabiaCorrespondence: Serene R Almuhaidib, Department of Dermatology, Dammam Medical Complex, Dammam, Saudi Arabia, Email SereneAlmuhaidib@gmail.comPurpose: Minimally invasive aesthetic procedures are widely popular among the youth. Despite their prevalence, there is a significant gap in the research concerning the relationship between these procedures and psychological wellbeing, as well as an insufficient exploration of the barriers and motivators influencing their adoption, this study aims to address these gaps.Methods: This cross-sectional study has utilized a secure online survey directed at Saudi university students as the target population. The survey was consisting of 18-item electronic questionnaire including of 4 parts (demographical data, history of psychological illness and screening of current psychological wellbeing using WHO-5 well-being tool, history of doing cosmetic procedure, or willingness to do in the future, barriers and motivators to do cosmetic procedures), and it was distributed across multiple social media platforms.Results: A total of 8443 college students completed the study questionnaire. Exactly 1096 (13%) of the students underwent a cosmetic procedure. The most reported procedures were laser hair removal (9.1%), filler (5.3%), skin boosters (2.8%), and Botulinum toxin A injections (Botox) (2.6%). The most ranked motivators were being painless, with no side effects (8.8 out of 10), followed by being free (8.0 out of 10) and enhancing self-confidence (7.4 out of 10).Conclusion: No significant difference recorded at the overall psychological well-being score between who underwent cosmetic procedures and who did not.Keywords: aesthetic procedures, cosmetic dermatology, cosmetic dermatologic procedures, psychological wellbeing, mental health, college students, Saudi Arabia